Prosperity with Sugar: A Strategy for Sustainable Livelihoods for Coconut Sap Farmers in the Pendekar CSR Program - Suci Trianingrum; Muhson Arifin; Primatika; Faries Fardian Anggoma; Ardi Maulana Mubarok (International Journal of Science and Society, 2023)
This article aimed to describe the sustainable livelihood strategy of coconut sap farmers in the PT Pertamina Patra Niaga Fuel Terminal Maos CSR Program of Karangsari Sap Tappers /Penderes Badeg Karangsari (Pendekar) in Karangsari Village, Adipala District, Cilacap Regency. The method employed in this study was qualitative with a theoretical approach to CSR, empowerment, and sustainable livelihoods. Informants in this study were determined by purposive sampling, which included 5 farmers and members of the Nira Cahaya Sejahtera Cooperative. The primary data was gathered through observation and interviews. while secondary data were obtained from CSR reports, related journals, and mass media which were then reduced and categorized based on certain themes and validated through triangulation. The results of this study indicate that 1) Coconut sap farmers in Karangsari Village already have the basic capital to survive by utilizing natural resources, specifically coconut trees which grow abundantly in Karangsari Village with a total area of 20 hectares. 2) The company provides assistance with five assets, including natural capital, human capital, financial capital, social capital, and physical capital in the coconut sap farmer empowerment Pendekar Program. 3) the SROI value for the Pendekar Program received by the company was 1: 2.33.